Coproduction of Food, Cultural Heritage and Biodiversity by Livestock Grazing in Swedish Semi-natural Grasslands - Eriksson, Ove (Frontiers in Sustainable Food Systems, 2022)
Livestock has been a backbone of people's livelihood as long as agriculture has existed in Scandinavia, c. 6,000 years. In the early Iron Age, c. 2,000 years ago, a land management system began to form, composed of infields (enclosed hay-meadows and crop fields) and outlying land used for livestock grazing. Despite many later innovations and societal changes affecting agricultural technology and practices, this way of organizing land use was a template for how landscapes were managed and structured until the modernization of agriculture and forestry during the last centuries. There are legacies of this historic land-use, mainly as “semi-natural grasslands” managed by livestock grazing (open or semi-open; long continuity of management; not much influenced by commercial fertilizers, plowing etc.). These semi-natural grasslands harbor an exceptional small-scale biodiversity, particularly plants and insects. Landscapes with semi-natural grasslands represent cultural heritage, and are appreciated for their beauty. The total area of semi-natural grasslands has declined considerably during the past 100 years, and the current trend suggest that further declines are expected. A large fraction of threatened biodiversity in Sweden thrives in these grasslands. Livestock grazing in semi-natural grasslands makes an important contribution to food production, and there is an increasing interest in consumption of products, mainly meat, from these grasslands. This implies that there is a positive feedback between food production, maintenance of biological diversity, and cultural heritage. This paper gives an overview of semi-natural grasslands, focusing on Sweden, from a historic, cultural and ecological perspective, and aims at discussing challenges and prospects for developing and maintaining positive associations between producing food, biodiversity, and cultural heritage, in the future.